2015
DOI: 10.1111/jpi.12284
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous ribonucleoprotein R regulates arylalkylamine N‐acetyltransferase synthesis via internal ribosomal entry site‐mediated translation in a circadian manner

Abstract: Rhythmic arylalkylamine N-acetyltransferase (AANAT) synthesis is a prominent circadian-controlled response that occurs in most mammals. AANAT is the core enzyme in melatonin production; because melatonin participates in many physiological processes, the regulation of AANAT is an important research topic. In this study, we focused on the role of heterogeneous ribonucleoprotein R (hnRNP R) in the translation of AANAT. A novel RNA-binding protein hnRNP R widely interacted with the 5' untranslated region (UTR) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…During IRES-mediated regulation, ribosomes are recruited directly to the 5′-UTR to process translation in a cap-independent manner 29 . Moreover, previous studies have suggested that cellular IRES-mediated translation occurs under specific stress conditions 30 31 32 and is required for robust oscillation of clock proteins 33 34 35 , which consolidates our suggested mechanisms.…”
supporting
confidence: 86%
“…During IRES-mediated regulation, ribosomes are recruited directly to the 5′-UTR to process translation in a cap-independent manner 29 . Moreover, previous studies have suggested that cellular IRES-mediated translation occurs under specific stress conditions 30 31 32 and is required for robust oscillation of clock proteins 33 34 35 , which consolidates our suggested mechanisms.…”
supporting
confidence: 86%
“…The presence of the above-mentioned RBDs suggests additional post-transcriptional roles. More importantly, hnRNP R is also found in the cytosol where it regulates cap-independent translation by binding to the IRES of target mRNAs (Lee et al 2015 ).…”
Section: Functional Diversity Of Hnrnpsmentioning
confidence: 99%
“…However, the most attention has been paid to the species-specific regulation of AA-NAT synthesis. The nocturnal elevation of AA-NAT activity is dependent on AA-NAT gene transcription [38] and the role of the RNA-binding protein heterogeneous ribonucleoprotein R (hnRNP R) in the translation of AA-NAT in rats [39]. However, in sheep [14,19,20], cattle [21] and humans [14], it mainly depends on changes in AA-NAT phosphorylation and post-translational modifications of the AA-NAT protein, such as proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%